P4 LEFT ATRIAL APPENDAGE ANATOMICAL CHANGES FOLLOWING RADIOFREQUENCY–BASED OSTIAL ISOLATION. (18th May 2022) - Magnocavallo, M; Della Rocca, D; Lavalle, C; Vetta, G; Mariani, M; Carola, G; Mohanty, S; Fengwei, Z; Tarantino, N; Aung, L; Alisara, A; Xiaodong, Z; et al.
Abstract: Background: Left atrial appendage (LAA) electrical isolation (ei) may be achieved via radiofrequency (RF) energy applications at the level of the appendage ostium targeting the sites of earliest activation recorded by a mapping catheter. Notably, RF has long been used in vascular, orthopedic, and aesthetic surgery to promote thermal–induced collagen matrix contraction, fibrosis, and tissue retraction. LAA anatomical changes associated to RF–induced tissue retraction have never been reported. Objective: To quantify the anatomical changes of the LAA ostium following RF–based LAAei. Methods: Thirty–four consecutive patients requiring AF ablation with LAAei underwent transesophageal echocardiography (TEE) within 7 days before (baseline TEE) and >6 months after (follow–up TEE) ablation. The diameter of LAA orifice and landing zone were measured at 4 different views (0°, 45°, 90°, 135°). Measurements were performed by two independent reviewers blinded to the patient's identity. Results: Among 34 AF patients (68±7yrs, 73.5% males), the LAA morphology was classified as chicken wing in 15 (44%) patients, windsock in 10 (29%), cactus in 6 (18%), and cauliflower in 3 (9%). At baseline TEE, the mean maximum and mean minimum ostial diameters were 25±4mm and 22±4mm, respectively. The mean maximum and mean minimum diameters of the landing zone were 26±4mm and 23±3mm, respectively. On average, LAAei was achieved after 16±7 minutes of RF at a power of 45–47W. Follow–up TEE was performed 257±148 days after LAAei. The median LAA contraction velocity was 0.1 m/s (IQR: 0.04–0.18) and was significantly impaired in all patients. At follow–up TEE, the mean maximum and mean minimum ostial diameters were 19±4mm and 17±3mm, respectively. The mean maximum and mean minimum diameters of the landing zone were 20±4mm and 18±4mm, respectively. The mean relative reduction of the ostium and the landing zone were –24.4% and –22.5%, respectively. Box–Whisker plots of the maximum and minimum ostial diameters before and after LAAei are reported in Fig. 1 . Conclusion: RF led to a > 20% reduction of the diameters of the ostium and the landing zone. These changes may have important implications for a successful percutaneous occlusion procedure and justify a staged approach of isolation and occlusion.